Relationship between Work and Family Conflict, Work-Autonomy and Work Exhaustion among IT Professionals - Ghayoor1, Pakeeza; Karamat2, Dr. Misbah; Gulab3, Iffat; Ali3, Syeda Zahra (ACADEMIA International Journal for Social Sciences, 2025)
The present study examined the relationship between work-family conflict, work autonomy, and work exhaustion among IT professionals. A purposive sampling technique was employed to collect data from various IT organizations, software houses, and IT universities across Pakistan. The sample comprised 300 participants, including 150 males and 150 females. Three psychometrically validated instruments were used: the Work and Family Conflict Scale (Netemeyer et al., 1996), the Work Design Questionnaire (Morgeson & Humphrey, 2006), and the Maslach Burnout Inventory (Maslach & Jackson, 1986). Data were analyzed using SPSS. Regression analysis indicated that work-family conflict significantly predicted work exhaustion. Correlational analysis revealed a significant positive relationship between work-family conflict and work exhaustion, while work autonomy was weakly correlated with work-family conflict. Independent samples t-tests indicated significant gender differences: females reported higher levels of exhaustion and work-family conflict, whereas males reported greater autonomy. Additionally, participants working fixed eight-hour shifts exhibited higher levels of autonomy and lower levels of exhaustion compared to those working variable or extended hours. These findings have practical implications for designing workplace policies, support systems, and training programs to reduce work-related stress and promote employee well-being within the IT sector.